Optimization and characterization of polysulfone membranes made of zinc oxide, polyethylene glycol and eugenol as additives - Harun, Z. (Taylors University, 2016)
The aim of this study to investigate the effect of zinc oxide, polyethylene glycol (PEG) and eugenol on the properties of membranes made of polysulfone (PSf). Polysulfone membranes were prepared via phase inversion method using N-methyl-2-pyrolidone (NMP) as a solvent and water as non-solvent. The membranes were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), atomic force microscopy (AFM), porosity, tensile strength, permeability, rejection and antibacterial test. The results were designed and optimized through a statistical approach using response surface methodology (RSM). The results showed that the use of zinc oxide and eugenol could improve membrane rejection and anti-bacterial property. The membrane permeability was found to increase with addition of PEG. The optimized dope formulation for maximum membrane permeability and rejection was found at 13.14 wt. PEG 5 wt. zinc oxide and 0.17 wt. eugenol. The permeability and rejection obtained for actual value is 866 L m-2h-1 and 91.0 respectively, which 1 and 2 difference compared to the predicted value.